The Browning critics - Litzinger, Boyd (University of Kentucky Press, 1965)
The poetry of Robert Browning has been the subject of extensive literary criticism since his death in 1889. Two well-known Browning scholars here present the best of Browning criticism, bringing together from many sources representative evaluations of the poet and his poetry. The twenty-one essays here have been arranged chronologically so that the reader can follow the development of Browning studies and the fluctuations of his poetic reputation. They express varied points of view and are typical of the critical methods used by the Browning scholars. Included are essays by George Santayana, J.